NATURAL MINERAL WATER ENRICHED WITH MAGNESIUM IN CHILDREN WITH CONSTIPATIONS - I. N. Zakharova; L. I. Elezova; L. L. Stepunina; L. A. Kataeva; N. A. Shmakov; I. B. Lagadze (Вопросы современной педиатрии, 2013)
Characteristics of medicinal mineral waters as well as the role of magnesium in human organism activity and normal functioning of the gastrointestinal tract are discussed in this article. Aim: to study the influence of mineral water enriched with magnesium on stool of children suffering from constipations, to determine the appropriate dosage and tolerance to such water and to research the effect of the combination of mineral and artesian drinking water on the functioning of the intestines of children with constipations. Patients and methods: 60 patients with chronic constipations (30 — in the study group and 30 — in control group) were included into the first study. Children from the study group were administered mineral water at the dosage of 3–5 ml/kg of the body weight 3 times per day, the treatment course was 10 days at hospital and after that — for 3 weeks in outpatient conditions. The second study included 45 children at the age of 3–15 years old, suffered from chronic constipations, who received sanatorium-and-spa treatment. Patients were divided into 2 groups: 25 were included into the main group, they were administered simultaneously medicinal mineral and artesian water. Mineral water was given at the dosage of 3–5 ml/kg of the body weight 3 times per day before eating. Artesian drinking water was given at the dosage of 6 ml/kg of body weight after eating. The duration of combination treatment was 21 days. Comparison group consisted of 20 children, receiving moderate mineral water. During the first study clinical examination of children was performed, the number of defecation was assessed and the blood samples were performed. During the second study clinical effect of mineral water in the form of regular formed stool was assessed. Results: data from the first study allow to recommend mineral water in treatment of children with chronic constipations as laxative agent at the dosage of 3–5 ml/kg of the body weight.  It should be received 15–20 minutes before eating at the full dosage 3 times per day. The course of treatment of chronic functional constipations in children must be at least 4 weeks. According to the results of the second study, combination administration of mineral and artesian water led both to normalization of the stool frequency and consistence and arresting of dyspeptic symptoms and abdominal syndrome, which often accompanied functional chronic constipations, as well as appetite improvement. Conclusions: including of mineral water into the scheme of treatment of chronic constipations and its combination with artesian water significantly increase the efficacy of therapy.Key words: children, mineral water, artesian water, gastrointestinal tract, chronic constipation, magnesium, mineralization, spa Rogashka Slatina, efficacy of treatment.